Second Language Teaching - Danesi, Marcel. author. aut Link
XI, 172 p.
Keywords: Second Language Teaching, A View from the Right Side of the Brain: -offers a practical introduction to the use of neuroscience to teach second languages; -provides information on the relation between how the brain learns and how this can be used to construct classroom activities; -evaluates methods, syllabi, approaches, etc. from the perspective of brain functioning; -illustrates how teaching can unfold with actual examples in several languages. This volume is indispensable in courses designed for language teachers, curriculum planners, and applied linguists.